Cypermethrin and Methomyl Resistance in Helicoverpa armigera (Hubner) - Upendhar, S.; Sree, K. Vani; Satyanarayana, J.; Singh, T. V. K. (International Journal of Economic Plants, 2017)
The H. armigera larvae of the Mahaboobnagar district recorded a LD50 of 29.125 µg larva-1 and 59.609 µg larva-1 at LD90 for cypermethrin. The LD50 and LD90 values of cypermethrin for Raichur population of H armigera was 32.481 and 38.172 µglarva-1, respectively. Toxicity of cypermethrin to Nagpur population of H. armigera showed that the LD50 and LD90 values were 20.069 and 54.708 µg larva-1, respectively, The chi-square test revealed that the population used in the study was homogenous (*p<0.05%). The H. armigera larvae of the Mahaboobnagar district recorded a LD50 of 3.651 µg larva-1 and 10.287 µg larva-1 at LD90 for methomyl. The LD50 and LD90 values of methomyl for Raichur population of H armigera was 3.630 and 10.417 µg larva-1, respectively, while Toxicity of methomyl to Nagpur population of H. armigera showed that the LD50 and LD90 values were 2.652 and 7.214 µg larva-1, respectively, when the chi-square test revealed that the population used in the study was homogenous (*p<0.05%). From, the results obtained we can conclude that the continuous application of same chemistries across the generations increases the resistance from F1 to F3. Alternating with the new chemistries results in no cross resistance development as it was observed in all the three populations.